Improving systems of care during and after a pregnancy complicated by hyperglycaemia: A protocol for a complex health systems intervention - D. MacKay; R. Kirkham; N. Freeman; K. Murtha; P. Van Dokkum; J. Boyle; S. Campbell; F. Barzi; C. Connors; K. O'Dea; J. Oats; P. Zimmet; et al. (BMC, 2020)
Abstract Background Many women with hyperglycaemia in pregnancy do not receive care during and after pregnancy according to standards recommended in international guidelines. The burden of hyperglycaemia in pregnancy falls disproportionately upon Indigenous peoples worldwide, including Aboriginal and Torres Strait Islander women in Australia. The remote and regional Australian context poses additional barriers to delivering healthcare, including high staff turnover and a socially disadvantaged population with a high prevalence of diabetes. Methods A complex health systems intervention to improve care for women during and after a pregnancy complicated by hyperglycaemia will be implemented in remote and regional Australia (the Northern Territory and Far North Queensland). The Theoretical Domains Framework was used during formative work with stakeholders to identify intervention components: (1) increasing workforce capacity, skills and knowledge and improving health literacy of health professionals and women; (2) improving access to healthcare through culturally and clinically appropriate pathways; (3) improving information management and communication; (4) enhancing policies and guidelines; (5) embedding use of a clinical register as a quality improvement tool. The intervention will be evaluated utilising the RE-AIM framework at two timepoints: firstly, a qualitative interim evaluation involving interviews with stakeholders (health professionals, champions and project implementers); and subsequently a mixed-methods final evaluation of outcomes and processes: interviews with stakeholders; survey of health professionals; an audit of electronic health records and clinical register; and a review of operational documents. Outcome measures include changes between pre- and post-intervention in: proportion of high risk women receiving recommended glucose screening in early pregnancy; diabetes-related birth outcomes; proportion of women receiving recommended postpartum care including glucose testing; health practitioner confidence in providing care, knowledge and use of relevant guidelines and referral pathways, and perception of care coordination and communication systems; changes to health systems including referral pathways and clinical guidelines. Discussion This study will provide insights into the impact of health systems changes in improving care for women with hyperglycaemia during and after pregnancy in a challenging setting. It will also provide detailed information on process measures in the implementation of such health system changes.